Principles of Financial Accounting - Jonick, Christine (Open textbook library., 2017)
The University of North Georgia Press and Affordable Learning Georgia bring you Accounting I. Well-written and straightforward, Principles of Financial Accounting is a needed contribution to open source pedagogy in the business education world. Written in order to directly meet the needs of her students, this textbook developed from Dr. Christine Jonick’s years of teaching and commitment to effective pedagogy. Features: Peer reviewed by academic professionals and tested by students Over 100 charts and graphs Instructional exercises appearing both in-text and for Excel Resources for student professional development This textbook is an Open Education Resource. It can be reused, remixed, and reedited freely without seeking permission.